2015
DOI: 10.1016/j.cub.2015.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Evidence Reveals that African and Eurasian Golden Jackals Are Distinct Species

Abstract: The golden jackal of Africa (Canis aureus) has long been considered a conspecific of jackals distributed throughout Eurasia, with the nearest source populations in the Middle East. However, two recent reports found that mitochondrial haplotypes of some African golden jackals aligned more closely to gray wolves (Canis lupus), which is surprising given the absence of gray wolves in Africa and the phenotypic divergence between the two species. Moreover, these results imply the existence of a previously unrecogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
209
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(241 citation statements)
references
References 27 publications
27
209
0
5
Order By: Relevance
“…A single Canis aureus haplotype has been reported from Egypt (Fig. 4) [15]. This specimen is from the Sinai Peninsula, close to the border between Egypt and Israel.…”
Section: Separation From Canis Aureusmentioning
confidence: 87%
See 3 more Smart Citations
“…A single Canis aureus haplotype has been reported from Egypt (Fig. 4) [15]. This specimen is from the Sinai Peninsula, close to the border between Egypt and Israel.…”
Section: Separation From Canis Aureusmentioning
confidence: 87%
“…Recent publications [13][14][15] have identified this animal as a separate species, more closely related to the Holarctic grey wolf than to the golden jackal. Gaubert et al [13] suggested the existence of both the golden jackal and African wolf in North and West Africa.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In total, 11,254 groups of orthologous genes were retained for comparative genomic analyses (Supplementary Table 9). We used published phylogenies of all included species to construct a fixed tree topology 104,105 used in all comparative genomic analyses ( Supplementary Fig. 8).…”
Section: Comparative Genomic Analyses Orthologue Identification and mentioning
confidence: 99%